Efektivitas Kinerja Pendamping Desa Berdikari Dalam Melaksanakan Tugas Pendampingan Desa Di Kota Pariaman - Yoseva, Widya (Universitas Sumatera Barat, 2023)
Implementation of Law Number 6 of 2014 concerning Villages means that the government provides assistance with the assistance of professional assistants who are experienced in the field of community empowerment and village development. Against this background, the Pariaman City Government is recruiting village assistants called Berdikari Village Assistants. This research uses qualitative research. The data used are primary data and secondary data as well as data collection techniques in the form of interviews and observations. The results of this research conclude the main tasks and functions of independent village assistants as well as the effectiveness of the performance of independent village assistants in the Village Government and Pariaman City Government. This is related to the process of assisting villages through facilitating villages in development planning and community empowerment, assisting villages in implementing village development, assisting villages in village community empowerment activities, facilitating and increasing the capacity of community groups, facilitating the structuring and development of village economic institutions, facilitating promotion, the results of village economic and tourism businesses, including village creative economic efforts and development of marketing networks for village economic business results, facilitating the development of village entrepreneurship, assisting innovative village development programs, submitting program implementation reports to the independent village assistance coordinator, as well as other duties provided by the Pariaman City Government so that the existence of independent village assistants is more contributing and effective.